2014
DOI: 10.1016/j.jelekin.2013.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Anticipatory postural adjustments during sitting reach movement in post-stroke subjects

Abstract: Abstract:The study assessed the effect of velocity of arm movement on the generation of APAs in the contralateral and ipsilateral muscles of individuals with stroke in the sitting position. In the sitting position, 10 healthy and 8 post-stroke subjects reached for an object placed at the scapular plane and mid-sternum height at self-selected and fast velocities. Electromyography was recorded from the anterior deltoid (AD), upper (UT) and lower trapezius (LT), and latissimus dorsi (LD). Kinematic analysis was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 27 publications
3
41
1
Order By: Relevance
“…21 The present study confirms that hemiparetic patients are able to voluntarily increase movement velocity. [16][17][18][19] The effect of target distance was significant in the fast condition but not in the preferred speed condition, in contrast with the results of several previous studies 23,36,52 which showed that hand velocity increased with movement distance in hemiparetic patients.…”
Section: Discussionmentioning
confidence: 83%
“…21 The present study confirms that hemiparetic patients are able to voluntarily increase movement velocity. [16][17][18][19] The effect of target distance was significant in the fast condition but not in the preferred speed condition, in contrast with the results of several previous studies 23,36,52 which showed that hand velocity increased with movement distance in hemiparetic patients.…”
Section: Discussionmentioning
confidence: 83%
“…), and stroke (Pereira et al . ). Therefore, this study has implications for informing the design of rehabilitation methods to focus on restoring and improving the timing and strength of APAs.…”
Section: Discussionmentioning
confidence: 97%
“…It has been demonstrated that the motor impairment following a stroke is partially due to changes in the anticipatory postural control (Slijper et al, 2002;Dickstein et al, 2004;Silva et al, 2012;Pereira et al, 2014). It should be also noted that trunk control at an early stage post stroke is one of the strongest predictors of upper-limb functional recovery (Hsieh et al, 2002).…”
Section: Tdcs In Neuro-rehabilitationmentioning
confidence: 99%